Analisa Pertumbuhan Ekspor Produk Primer Indonesia dengan Pendekatan Dekomposisi Shift Share - Aji, Sofyan (Cendekia Niaga, 2024)
Shift-Share analysis is a method to decompose total changes in economic indicators into various components/indicators which are sources of growth or decline. This analysis is used, among other things, to see economic growth through industrial mix components, and the competitiveness of labor in a region. By using decomposition analysis per component, this analysis can be applied to international trade analysis. This paper analyzes changes or "shifts" in the share of trade (especially exports), and uses Global, Sectoral, Geographical and Product Competitiveness indicators. In contrast to simple export growth analysis, with the formula , which only looks at the total value of indicators in year compared to , this method shows what sectors/industries are experiencing changes , and the influence of sector competitiveness on total exports. The sector chosen in this research is the primary sector with a 2-digit HS group, namely (1) Fish and Crustaceans, Molluscs and Other Aquatic Invertebrates; (2) Coffee, Tea, Maté and Spices; (3) Animal, Vegetable or Microbial Fats and Oils and Their Dissociation Products; (4) Preparations from Meat, from Fish, from Crustaceans, Mollusks or Other Aquatic Invertebrates; (5) Preparations from Cereals, Flour, Starch or Milk; Cake Industry Products; and (6) Various Edible Processings. The export destination countries studied are countries in the Southeast Asia region. The results of the research show that the primary export sector is positively influenced by the effects of changes in global exports, product sector mix effects, and geographic effects, as well as negatively influenced by the competitiveness component. It is hoped that the results of this research can be an evaluation for exporters that although there has been an increase in exports, this increase is not caused by an increase in competitiveness. So treatment is needed to increase competitiveness which can influence the increase in Indonesian exports.